Impact of Cashless Transaction on Consumer Spending Habits and Consumer Satisfaction: A Case of Nepal - Karn, Shreya; Pradhan, Sumit (Nepalese Journal of Finance, 2025)
The study examines the impact of cashless transaction on consumer satisfaction and consumer spending habits in Nepal. Consumer satisfaction and consumer spending habits are dependent variables. The selected independent variables are ease of use, security, perceived usefulness, convenience, security, trust and fee charge. The primary source of data is used to assess the opinions of respondents regarding ease of use, security, perceived usefulness, convenience, security, trust, fee charge, consumer satisfaction and consumer spending habits. The study is based on primary data of 160 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation and multiple regression models are estimated to test the significance and importance of cashless transaction on consumer satisfaction and consumer spending habits. The study showed that several factors positively impact consumer spending habits and satisfaction with cashless transactions in Nepal. The easier cashless transactions are to use, the more consumers spend and the more satisfied they are. Better security measures make consumers feel more confident, leading to increased spending and greater satisfaction. When consumers find cashless transactions useful, they tend to spend more and are more satisfied. The more convenient cashless transactions are, the more they influence consumers to spend and the higher their satisfaction. Higher levels of trust in cashless transaction systems encourage more spending and greater satisfaction. Additionally, lower or reasonable fees associated with cashless transactions lead to higher consumer spending and increased satisfaction. Overall, ease of use, security, perceived usefulness, convenience, trust, and reasonable fees all play a significant role in shaping consumer spending habits and satisfaction in Nepal’s cashless transaction landscape.